Outcome or Process Regret in Online Purchasing: Consequences of Brand Trust to Consumer Purchase Regret - Zulkarnain Zulkarnain; Eka Danta Jaya Ginting; Ferry Novliadi; Surya Siahaan (International Journal of Supply Chain Management, 2019)
Nowadays online purchasing is one of the most popular internet activities. Various types of online products that are often purchased by consumers. Some factors in online purchases are availability access, and time efficiency. When consumers purchase an online product, there are certain expectations as regards its uses/functions. They will experience post-purchase regrets if the product is not in accordance with the initial expectations. These regrets are due to outcome purchase and process purchase. This study was carried out having two major objectives. First was to find out the influence of brand trust on consumer purchase regret. Second was to examine brand reliability and brand intentions were determinants of outcome and process regret. The questionnaire was employed for the collection of data, and this involved 305 participants. The result confirmed that brand trust was a significant influence on consumer regret in online purchasing. It also revealed that brand reliability of online product to be a major predictor of reducing consumers’ outcome and process regrets. These findings indicated that a brand plays a vital role in becoming an identifiable online product and protects consumers from unpleasant psychological stages.